Optimized Sizing, Selection, and Economic Analysis of Battery Energy Storage for Grid-Connected Wind-PV Hybrid System. (24th December 2015) - Fathima, Hina; Palanisamy, K.
Abstract : Energy storages are emerging as a predominant sector for renewable energy applications. This paper focuses on a feasibility study to integrate battery energy storage with a hybrid wind-solar grid-connected power system to effectively dispatch wind power by incorporating peak shaving and ramp rate limiting. The sizing methodology is optimized using bat optimization algorithm to minimize the cost of investment and losses incurred by the system in form of load shedding and wind curtailment. The integrated system is then tested with an efficient battery management strategy which prevents overcharging/discharging of the battery. In the study, five major types of battery systems are considered and analyzed. They are evaluated and compared based on technoeconomic and environmental metrics as per Indian power market scenario. Technoeconomic analysis of the battery is validated by simulations, on a proposed wind-photovoltaic system in a wind site in Southern India. Environmental analysis is performed by evaluating the avoided cost of emissions.